1991
DOI: 10.1104/pp.95.3.943
|View full text |Cite
|
Sign up to set email alerts
|

Ethylene Production by Growing and Senescing Pear Fruit Cell Suspensions in Response to Gibberellin

Abstract: A pear (Pyrus communis L. cv Passe Crassane) cell suspension was used as a model system to study the influence of gibberellin on processes related to fruit ripening. Growth of the cell cultures was inhibited and their loss of viability was accelerated when 0.5 millimolar gibberilic acid (GA3) was added to suspensions at two stages of cell development, namely, growth and quiescence. Cell respiration rate was unaffected up to 2 millimolar GA3 but ethylene production, both basal and 1-aminocyclopropane-1-carboxyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
2

Year Published

1994
1994
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 15 publications
0
1
0
2
Order By: Relevance
“…Os resultados apresentados na Figura 1 deixam claro que não houve aumento significativo do etileno em conseqüência do corte e da infiltração, o que depõe a favor do método de infiltração por imersão. Em outros sistemas modelo, como por exemplo, na suspensão de células de pêra, foi observado que o ácido giberélico pode inibir a produção de etileno, reduzindo em até 33% o nível de etileno basal no meio de cultura tratado com 1mM GA 3 [2].…”
Section: -Respiração E Etileno Durante O Amadurecimento Da Bananaunclassified
See 1 more Smart Citation
“…Os resultados apresentados na Figura 1 deixam claro que não houve aumento significativo do etileno em conseqüência do corte e da infiltração, o que depõe a favor do método de infiltração por imersão. Em outros sistemas modelo, como por exemplo, na suspensão de células de pêra, foi observado que o ácido giberélico pode inibir a produção de etileno, reduzindo em até 33% o nível de etileno basal no meio de cultura tratado com 1mM GA 3 [2].…”
Section: -Respiração E Etileno Durante O Amadurecimento Da Bananaunclassified
“…Dentre eles, o etileno é de longe o mais estudado devido a sua importância na maturação e senescência de folhas, flores e frutos [2]. Este processo depende em parte do aumento da sensibilidade ou da diminuição da resistência do fruto à ação do etileno e também do desaparecimento, ou inativação, de alguns fitoreguladores [7].…”
Section: -Introduçãounclassified
“…Gibberellins are used in commercial fruit production to modify fruit set and to delay maturation and ripening (Ben-Arie and Ferguson 1991). Several authors have observed that the exogenous addition of gibberellic acid (GA3) retards chlorophyll degradation in citrus (Biale 1978), apricot (Abdel-Gawad and Romani 1974), and mango (Khader et al 1988).…”
mentioning
confidence: 99%